Laparoscopic versus open resection for colorectal liver metastases: a single-center study with propensity score analysis - de'Angelis, Nicola; Eshkenazy, Rony; Brunetti, Francesco; Valente, Roberto; Costa, Mara; Disabato, Mara; Salloum, Chady; Compagnon, Philippe; Laurent, Alexis; Azoulay, Daniel (Journal of laparoendoscopic & advanced surgical techniques. Part A, 2015)
The aim of the study was to compare the long-term oncologic results of laparoscopic liver resection (LLR) versus open liver resection (OLR) for colorectal liver metastasis (CRLM) using a propensity score analysis. This propensity score matching (PSM) study was based on a prospective database of a single tertiary-care center. Patients with primarily resectable CRLM were selected for a 1:1 PSM between LLR and OLR. Covariates for PSM estimation were age, gender, body mass index, American Society of Anesthesiologists score, primary tumor location, CRLM presentation, location, size, and number. Moreover, the year of surgery was included in the PSM model. Operative, postoperative, and survival rates were compared between groups. From 2000 to 2013, in total, 339 liver resections for CRLM met the selection criteria. Among these, 52 LLR patients were matched with 52 OLR patients. The two surgical approaches showed similar postoperative morbidity and mortality rates. LLR was associated with significantly less blood loss, less frequent need for and shorter duration of pedicle clamping, faster recovery, and shorter hospital stay. Moreover, the overall 3- and 5-year survival rates were, respectively, 83% and 76% for LLR and 87% and 62% for OLR (P=.51). The 3- and 5-year disease-free survival rates were, respectively, 28% and 21% for LLR and 31% and 21% for OLR (P=.71). The LLR achieves similar oncological results to those of the standard open surgery for CRLM, with the additional benefit of significantly faster recovery.